The perception and satisfaction of customers towards the service quality provided by De Rhu Beach Resort, Kuantan / Nor Liza Marjoni (Faculty of Business Management, 2005)
Customer's satisfaction is an ultimate important factor in the service industry and has be given priority by most of the organization today as their competitive advantages to win customers. This project paper is mainly focus on the service quality provided by De Rhu Beach Resort in creating and enhancing customers' satisfaction. The primary objective of this study is try to seek and identify the level of customer perception towards the service quality ofDRBR and the level of satisfaction towards the service received. As DRBR has been awarded as a four star hotel, it is important for the company to considered and concern on the customer satisfaction as customer satisfaction will leads to an organization success. Finally, this project paper will also highlight general recommendations to De Rhu Beach Resort in delivering a high quality service to their customers.